Complications from microfocused transcutaneous ultrasound: Case series and review of the literature. Issue 1 (20th November 2017) - Friedmann, Daniel P.; Bourgeois, Gregory P.; Chan, Henry H.L.; Zedlitz, Ann C.; Butterwick, Kimberly J.
Abstract : Background and Objective: Microfocused ultrasound (MFUS) technology has been utilized since 2009 for improvement in mild to moderate skin and soft tissue laxity of the face and neck. Few complications have been previously reported, the majority of which include mild and transient erythema, edema, ecchymosis, and nerve paralysis. Rare yet serious potential complications of MFUS for noninvasive skin tightening of the face and neck are, however, possible. Methods & Materials: Retrospective multicenter case series of five patients from the authors' practice who developed serious adverse events directly related to MFUS with a commercially available device (Ultherapy; Merz North America, Inc., Raleigh, NC). Results: Five patients developed blistering, erosion/ulceration, cutaneous, or subcutaneous tissue edema with resulting atrophy, and/or cutaneous necrosis following single sessions of MFUS. Conclusion: Despite their rarity, serious adverse events secondary to MFUS are nevertheless possible and may be underreported. Early management of complications includes local wound care, patient reassurance, and topical corticosteroids and/or pulsed‐dye laser to mitigate inflammatory sequelae. Other cosmetic and surgical therapies should be utilized when conservative measures have failed. Lasers Surg. Med. 50:13–19, 2018. © 2017 Wiley Periodicals, Inc.